Angiogenic factors in human proliferative sickle cell retinopathy - Cao, J. (1999)
BACKGROUND/AIMS—Preretinal neovascular formations called sea fans develop at the border of non-perfused peripheral retina in sickle cell retinopathy. Angiogenic factors which could contribute to their development, however, have not been examined previously. The objective of this study was to determine immunohistochemically if vascular endothelial growth factor (VEGF) or basic fibroblast growth factor (bFGF) were associated with sea fan formations. METHODS—Immunohistochemistry on cryosections was used to localise bFGF, VEGF, heparan sulphate proteoglycan, human serum albumin, collagens IV and II, and von Willebrand factor in tissue from five sickle cell and one control subject. RESULTS—The greatest immunoreactivity for VEGF and bFGF was in the feeder and preretinal vessels of sea fans (p<0.01). The most prominent reaction product was localised to vascular endothelial cells. In retinal vessels, VEGF and bFGF immunoreactivities were greater in sickle cell subjects (both proliferative and non-proliferative) than in the control subject (p<0.01 and p<0.02 respectively). In the sickle cell retina, no angiogenic factor immunoreactivity was detected in non-perfused periphery and there was no significant difference in bFGF or VEGF immunoreactivity between perfused retina and the border of perfused and non-perfused areas. CONCLUSION—Our results demonstrate for the first time that VEGF and bFGF are associated with sea fan formations in sickle cell retinopathy. Both factors may function in an autocrine manner because immunoreactivity for these factors was greater within the neovascularisation than in adjacent retina.